Solution of Integral Equation via Orthogonally Modified F-Contraction Mappings on O-Complete Metric-Like Space - Prakasam, Senthil Kumar; Gnanaprakasam, Arul Joseph; Kausar, Nasreen; Mani, Gunaseelan; Munir, Mohammed; Sala, Huddin (KOREAN INST INTELLIGENT SYSTEMS, 2022)
This study introduces the concepts of orthogonally modified F-contraction of type-I and type-II and certain fixed-point theorems for self-mapping in orthogonal metrics, such as space, have been proved. The proven results generalize and extend some well-known results in the literature. The application of the main results has been presented.
Keywords: Orthogonal set; Orthogonally modified F-contraction of type-I; Type-II; Fixed point; Computer Science